A Practical Guide to Molecular Dynamics Simulations of DNA Origami Systems - Jejoong Yoo; Chen-Yu Li; Scott Michael Slone; Christopher Maffeo; Aleksei Aksimentiev (DNA Nanotechology: Methods and Protocols, 2018)
The DNA origami method exploits the self-assembly property of nucleic acids to build diverse nanoscale systems. The all-atom molecular dynamics (MD) method has emerged as a powerful computational tool for atomic-resolution characterization of the in situ structure and physical properties of DNA origami objects. This chapter provides step-by-step instructions for building atomic-scale models of DNA origami systems, using the MD method to simulate the models, and performing basic analyses of the resulting MD trajectories.